The temporal distribution and relative abundance of stable flies (Stomoxys calcitrans) (Diptera : Muscidae) in a feedlot near Heidelberg, Gauteng, South Africa - Evert, Maria Magdalena (North-West University, 2014)
The stable fly, Stomoxys calcitrans (L.) is a haematophagous fly that feeds primarily on the forelegs of cattle stimulating a range of avoidance behaviours in confinement situations such as feedlots. From literature it is apparent that stable flies associated with feedlots have a significant impact on cattle especially with regard to economic parameters such as a decline in feed intake and thus a lower average daily gain resulting in less meat production due to irritation caused by painful bites. The abundance of the stable flies was studied in a large commercial feedlot near Heidelberg from October 2012 to September 2013. Two tsetse fly traps, namely the NZI and the Vavoua fly traps, were used and evaluated in determining the seasonal abundance of the stable flies. The tsetse traps proved to be most effective for sampling stable flies compared to other designs. The NZI and Vavoua tsetse type trap were compared and although there were no significant difference the NZI trap proved to be more reliable and user friendly for this study. Stable flies were more abundant from late December with a peak in numbers late in January through February and became less abundant from early March. Minimum to no fly abundance occurred in the winter months from May to June 2013. The data indicated a strong edge effect for the stable flies, the flies were more abundant in pens and corridors that were surrounded by vegetation, manure run off and holding ponds. The numbers collected in traps were correlated with stable fly counts on the cattle to be used in calculating a future threshold in chemical control. Preliminary observations on the influence of temperature, wind speed and rainfall were also made. This research will form part of a larger project to determine an integrated fly management program for the feedlot.
MSc (Environmental Sciences), North-West University, Potchefstroom Campus, 2014
Keywords: Stomoxys calcitrans; Stable flies; Feedlots; Meat production; Seasonal abundance; South Africa; Stalvlieë; Voerkrale; Vleisproduksie; Seisoenale voorkoms; Suid-Afrika